2017
DOI: 10.1530/rep-17-0441
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of miRNAs in porcine germ cells during spermatogenesis

Abstract: Spermatogenesis includes mitosis of spermatogonia, meiosis of pachytene spermatocytes and spermiogenesis of round spermatids. MiRNAs as a ~22 nt small noncoding RNA are involved in regulating spermatogenesis at post-transcriptional level. However, the dynamic miRNAs expression in the developmental porcine male germ cells remains largely undefined. In this study, we purified porcine spermatogonia, pachytene spermatocytes and round spermatids using a STA-PUT apparatus. A small RNA deep sequencing and analysis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
0
19
0
5
Order By: Relevance
“…These observations led us to hypothesize that boar SP-EVs may participate in porcine spermatogenesis. Ssc-miR-10a-5p is highly expressed in spermatogonia (43) and is also abundant in the SP-EVs, suggesting that boar SP-EVs may partially derive from testis and influence spermatogenesis. The miRNA ssc-miR-200b has been shown to target porcine spermatogenesis-associated serine-rich 2-like (SPATS2L) gene, which significantly affects litter size (44), suggesting that boar SP-EVs may affect sperm function and influence embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…These observations led us to hypothesize that boar SP-EVs may participate in porcine spermatogenesis. Ssc-miR-10a-5p is highly expressed in spermatogonia (43) and is also abundant in the SP-EVs, suggesting that boar SP-EVs may partially derive from testis and influence spermatogenesis. The miRNA ssc-miR-200b has been shown to target porcine spermatogenesis-associated serine-rich 2-like (SPATS2L) gene, which significantly affects litter size (44), suggesting that boar SP-EVs may affect sperm function and influence embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted using RNAiso Plus reagent (TaKaRa, Dalian, China). RT-qPCR was performed as described previously using the primers listed in Supplementary Table S1 ( Chen et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Small RNA-Seq and analysis were performed as previous report [26]. Briefly, total RNA was used for adaptor ligation, first strand cDNA synthesis and PCR amplification to construct small RNA libraries.…”
Section: Small Rna-seq and Analysismentioning
confidence: 99%
“…To further analyze the expression pattern of miRNAs in SCs, we compared SC seq dada with small RNA data from germ cells (GSE124099) that was reported previously [26]. Principal component analysis (PCA) revealed that three SC samples clustered together ( Fig.…”
Section: Analysis Of Mirna Expression In Scs and Germ Cellsmentioning
confidence: 99%